Permanência, mudança ou silenciamento: o que os livros de Geografia para o ensino fundamental dizem(ou não) acerca das pessoas com deficiência? - Reinaldo de Freitas (2015)
The inclusion of disabled people in several sectors of society is a relatively recent paradigm in Brazil. Since the 1990s, the term inclusion began to designate actions through which society organizes itself in order to cater to the needs of people with disability, aiming at enabling coexistence for everyone within the same system. Since 1998, according to the school census carried out by INEP, the number of enrollments of disabled students in regular classes has gradually increased, demanding a quick response from the educational system so as to makeinclusion effective and to provide quality education for all. The production of textbooks adapted to this new context in an important action in this process, through the broadcasting of positive representations of diversity in our society. In the construction of an inclusive educational project, a set of laws guaranteeing the rights of people with disability in Brazil has beenelaborated in the last two decades. In addition, it would be coherent that the legal framework shaping the production of pedagogical material considered these new norms. This research aims at identifying how resources, both in official documents (notices and textbook guides) and in textbook collections on Geography since the book is a producer of meanings, result of an educational project and subject to several impositions from the market (TONINI, 2003), respond to the changes promoted by inclusion policies in Brazil. In order to do so, textbookcollections were selected according to their presence in all editions of the National Program for Textbooks (PNLD, in Portuguese) aiming at better following the changes in treatment of this theme, identifying the reflections of the legislation conceived around the representation in oursociety and, therefore, identifying the inclusion of people with disability and issues related to promoting citizenship. Four alternate collections were selected from PNLD due to the belief that significant modifications might be identified in them. Thus, this research analyses the booksof two textbook collections targeted to the 6th and 7th grades of Middle School grades for which the themes designated by the National Curricular Parameters (PCNs, in Portuguese) may contemplate disabled people in PNLD editions from 1999, 2005, 2011 and 2014. Asmethodological background for the analysis of documents and pedagogical materials, Discourse Analysis was chosen because such a methodology values what is said and retained by society from speech (CHARAUDEAU; MAINGUENEAU, 2014). Other studies considered include Faria (2009), Fiorin (2013), Gregolin (1995), among others. From the identification of theme and pictures, highlighted excerpts from notices and guides for choosing textbooks and the semantic trajectory designed by the analysis carried out in this research, results indicate thatnotices cast great influence in the conformity of representation towards segments of our society, lacking a more incisive reformulation in order to promote more adjusted representations for the reality of schools and society in a broader sense.